The Right to Avoid Self-incrimination: Yet Another Elephant in the Automated Competition law Enforcement Room? - Pieter Van Cleynenbreugel (European Papers)
(Series Information) European Papers - A Journal on Law and Integration, 2024 9(3), 978-997 | Article | (Table of Contents) The right to avoid self-incrimination forms part of the fundamental rights of the defence accompanying the public enforcement of European Union (EU) competition law. Thanks to this right, undertakings cannot be forced to produce guilt-admitting answers to the European Commission or national competition authorities applying arts 101 and 102 of the Treaty on the Functioning of the European Union (TFEU). Despite its general recognition, open questions relating to its scope and importance throughout enforcement procedures constrain its practical use. Although those questions are problematic as a matter of EU law in general, this Article submits that they also have a direct and significant impact on the ability for EU and Member States’ competition authorities to introduce artificial intelligence-backed enforcement tools. Against such background, the Article prospectively analyses how the right to avoid self-incrimination could constrain the design and use of tailored automated competition enforcement tools. The first part of the Article revisits the scope of the right to avoid self-incrimination as apparent from the Court of Justice of the European Union’s case law. It identifies and distinguishes three open questions which underlie the right’s application in EU competition law enforcement. The second part argues that those questions directly condition the ways in which artificial intelligence-backed public enforcement tools can be implemented at different stages of the investigation and decision-making. Anticipating litigation on those questions, the Article therefore calls for the right to avoid self-incrimination to be given more explicit attention when designing or introducing automated enforcement tools. | (Abstract) I. Introduction. – II. The right to avoid self-incrimination in EU competition law. – II.1. The right to avoid self-incrimination in the Charter of Fundamental Rights: Article 6 ECHR as a starting point. – II.2. A specific right to avoid self-incrimination in EU competition law enforcement? – III. Protection against self-incrimination and automated competition law enforcement. – III.1. Automated competition law enforcement as an emerging reality. – III.2. Three automated enforcement scenarios calling for increased attention to self-incrimination avoidance. – III.3. Future-proofing competition law enforcement requires future-proofing the right to avoid self-incrimination. – IV. Conclusion.